EFEKTIVITAS BIMBINGAN KELOMPOK DENGAN TEKNIK DISKUSI KELOMPOK UNTUK MENCEGAH FOMO BERLEBIHAN PADA MAHASISWA BOJONOGORO - Riski Putra Ayu Distira; Ah. Fahri Munir; Zeti Novitasari (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2026)
The purpose of this study was to assess the effectiveness of group counseling using the group discussion technique in preventing excessive Fear of Missing Out (FoMO) behavior among students in Bojonegoro. Group counseling with the group discussion technique aims to help students understand the negative impacts of FoMO, increase self-awareness regarding social media use, and develop critical thinking and self-control skills through interaction and open exchange of ideas within the group. This study employed a quantitative pre-experimental approach with a one-group pretest-posttest design. The research subjects consisted of ten students from the Guidance and Counseling Study Program in Bojonegoro, selected through purposive sampling. Data were collected using a FoMO scale that had been tested for validity and reliability. Data analysis was conducted using a paired sample t-test to determine the difference in FoMO levels before and after the treatment. The results showed a significant difference between FoMO scores before and after the implementation of group counseling with the group discussion technique, with a t-value of 11.354 and a significance level (2-tailed) of 0.000 < 0.05. This confirms that group counseling using the discussion technique is an effective intervention in addressing psychological challenges in the digital era such as FoMO and is relevant to be applied in school-based mental health programs.